Reuse of low quality water in Egypt - Mostafa H.; El Gamal F.; Shalby A. (Non-conventional water use: WASAMED project, 2005)
In Egypt, the reuse of the drainage water can be natural, official and non-official reuse. Natural reuse of drainage water occurs where rivers or canals act as a drain for hydrologic basin aquifer systems. Official reuse is the practice of including part of drainage water flow in the quantity of irrigation water delivered by the irrigation system. Non-official reuse is practiced by individual farmers who decide when and how much drainage water will be used for supplementing their irrigation water supply. In addition to these issues, the present article discusses the three national projects of drainage water reuse (Al- salam canal, Omonm drain and drain No 1 and 2) as well as the factors that may adversely affect the drainage reuse in the Delta region, including pollution, irrigation improvement program implementation, rice area reduction, and the main health risks caused by discharges of insufficiently treated wastewater to rivers and drains.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)